MOLECULAR ANALYSES FOR GENETIC POLYMORPHISMS OF THE LPL GENE AND THEIR ASSOCIATIONS WITH INTRAMUSCULAR FAT CONTENT IN GOATS - Yinghui Ling; Kangyan Wang; Jie Yin; Long Zhu; Xiaorong Zhang; Chunyang Han; Jianping Ding (Journal of Animal and Plant Sciences, 2015)
The experiment was conducted to determine the genetic relationship between polymorphism of lipoprotein lipase(LPL) gene and intramuscular fat content in goat. 337 goats were collected from 6 goat populations including Anhui white goats, Boer goats, Linqu dairy goats, Minshan black fur goats, Jining grey goats and Matou goats. The genetic variations in exon 1,6, and 7 of LPL gene were detected by PCR-SSCP. Genetic effect of LPL gene on intramuscular fat content was analyzed by Anhui White and Boar populations. The results exhibited as follows: one polymorphism site was found in the exon1 of LPL and five genotypes were defined. Besides that, one polymorphism site was found in exon 6 and 7 of LPL gene, respectively, andthree genotypes AA, AB and BB were defined in both of exon 6 and 7. LPL gene increased intramuscular in the order of P1 (exon 1 of LPL): BB>AB>AA, P6 (exon 6 of LPL): AA>AB>BB, and P7 (exon 7 of LPL): BB>AB>AA. These results indicated that LPL gene could be considered as a candidate gene affecting intramuscular fat content in special goat populations.
Keywords: Goat; Lipoprotein lipase gene; Intramuscular fat content; PCR-SSCP